1994
DOI: 10.1128/aac.38.11.2564
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria: a major pathogenic factor for anastomotic insufficiency

Abstract: The aim of this study was to determine the influence of bacteria on the development of anastomotic insufficiency following gastrectomy in the rat. Fifty-seven male Wistar rats were randomly assigned to three groups and subjected to gastrectomy. Group I (n = 20) was orally inoculated with 109 Pseudomonas aeroginosa organisms on postoperative day 1. Group II (n = 20) served as the control group. Group III (n = 17) was decontaminated with 320 mg of tobramycin, 400 mg of polymyxin B, and 500 mg of vancomycin per l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 19 publications
2
40
0
3
Order By: Relevance
“…In the colons prepared with neomycin and erythromycin, which were continued into the postoperative period, no adverse effect of the in induced ischemia and no AL was found [4]. These results lend support to the results of Cohn [5] and Le Veen [11], and, We carried out the first animal experiments examining the protective effect of topical antibiotic prophylaxis following upper gastrointestinal surgery and were the first to suggest that P. aeruginosa might play a causative role in AL [20]. In the latter trial, rats undergoing total gastrectomy were orally inoculated with P. aeruginosa on postoperative day 1, in order to contaminate the anastomoses.…”
Section: Historical Studiessupporting
confidence: 74%
See 1 more Smart Citation
“…In the colons prepared with neomycin and erythromycin, which were continued into the postoperative period, no adverse effect of the in induced ischemia and no AL was found [4]. These results lend support to the results of Cohn [5] and Le Veen [11], and, We carried out the first animal experiments examining the protective effect of topical antibiotic prophylaxis following upper gastrointestinal surgery and were the first to suggest that P. aeruginosa might play a causative role in AL [20]. In the latter trial, rats undergoing total gastrectomy were orally inoculated with P. aeruginosa on postoperative day 1, in order to contaminate the anastomoses.…”
Section: Historical Studiessupporting
confidence: 74%
“…Germfree rats also had highly significantly lower AL rates than normal controls using topical antibiotics (p = 0.0002) [21]. We concluded that in addition to poor surgical technique and impaired blood supply to the intestinal anastomosis, bacteria play a major role in the pathogenesis of AL [20].…”
Section: Historical Studiesmentioning
confidence: 99%
“…Almost 40 years later in 1994, a study group identified Pseudomonas aeruginosa as a possible microbial agent associated with leakage after a gastrectomy in rats (17). In this study, rats were allocated into three groups: the first group was inoculated with P. aeruginosa, the second was a control group, and the third was decontaminated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, Steven Cohn performed a similar study in rats showing that oral antibiotics prevented anastomotic leaks completely in devascularized colon segments with complete healing and resolution of ischemia [18]. A seminal study reconfirming the role of microbes as causative agents was then performed in 1994 when Schardey et al demonstrated that introduction of pathogenic bacteria to a newly formed rat anastomosis directly causes anastomotic leak [19]. In a clinical followup, his group then performed a multi-center placebo-controlled, blinded prospective randomized clinical trial (RCT) in 1996 demonstrating that oral decontamination prevent anastomotic leak following gastro-esophageal surgery [20].…”
Section: Anastomotic Leak As An Infectious Diseasementioning
confidence: 99%